2014
DOI: 10.1136/archdischild-2014-306626
|View full text |Cite
|
Sign up to set email alerts
|

Time spent in different types of childcare and children's development at school entry: an Australian longitudinal study

Abstract: More time in centre-based childcare (but not other types of care) through the first 3 years of life was associated with higher parent-reported and teacher-reported externalising problem behaviours, and lower parent-reported internalising problem behaviours but not with children's receptive vocabulary ability at school entry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 29 publications
2
14
0
Order By: Relevance
“…However, we did find that more days in daycare was associated with more caregiver‐rated externalizing behaviour problems, although this effect decreased to non‐significance when predicting externalizing behaviour one year later at age 3 years, when controlling for externalizing behaviour at age 2 years. This slight negative behavioural association with the amount of daycare is consistent with results from the NICHD studies (Belsky et al, ; NICHD ECCRN, , ) and several other studies (Gialamas et al, ; Loeb et al, ; Yamauchi & Leigh, ). Although attachment insecurity and emotion regulation problems have been suggested as possible explanations for these findings (for a critical review, see McCartney et al, ), the supporting evidence for these claims is limited (e.g., NICHD ECCRN, ).…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…However, we did find that more days in daycare was associated with more caregiver‐rated externalizing behaviour problems, although this effect decreased to non‐significance when predicting externalizing behaviour one year later at age 3 years, when controlling for externalizing behaviour at age 2 years. This slight negative behavioural association with the amount of daycare is consistent with results from the NICHD studies (Belsky et al, ; NICHD ECCRN, , ) and several other studies (Gialamas et al, ; Loeb et al, ; Yamauchi & Leigh, ). Although attachment insecurity and emotion regulation problems have been suggested as possible explanations for these findings (for a critical review, see McCartney et al, ), the supporting evidence for these claims is limited (e.g., NICHD ECCRN, ).…”
Section: Discussionsupporting
confidence: 89%
“…However, several other studies found no relation with extensive time in child care or preschool and children's negative behavioural outcomes in the early years (Barnes, Leach, Malmberg, Stein, & Sylva, ; Romano, Kohen, & Findlay, ; Votruba‐Drzal, Coley, Maldonado‐Carren, Li‐Grining, & Chase‐Lansdale, ; Zachrisson, Janson, & Naerde, ). When comparing these studies, it seems that the most consistent negative behavioural associations are found for teacher reports (Gialamas et al, ; Loeb et al, ; NICHD ECCRN, ) and for families from relatively high SES families (Loeb et al, ; Yamauchi & Leigh, ). Thus, these mixed findings appear to be partially due to variations in study designs, such as differences in informants and sample characteristics.…”
Section: Introductionmentioning
confidence: 95%
See 2 more Smart Citations
“…Children from disadvantaged areas have the most to gain from ECEC experiences34 but, in our population, attendance per se did not appear to close the disadvantage gap. A recent Australian-based study has shown that in the ECEC setting, the quality of relationships between carers and children strongly modifies the association between income and developmental outcomes,35 suggesting that promoting high-quality relationships may be an effective strategy for closing this gap.…”
Section: Discussionmentioning
confidence: 99%